The UN Security Council and informal groups of states complementing or competing for governance? - Prantl, Jochen, 1967- (Oxford : Oxford University Press, 2006)
This work offers the first comparative treatment of the roles of informal ad hoc groupings of states, such as Groups of Friends or G-8 within selected conflict settings, and their effects on the practices of the UN Security Council.
Includes bibliographical references and index.
Description based on print version record.
Keywords: United Nations. -- Security Council; Conflict management; International cooperation; International relations; National security